2006
DOI: 10.1080/01496390600641546
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modelling and Process Control of ZnS Precipitation

Abstract: This paper presents the dynamic modelling and design of a control strategy for the ZnS precipitation process. During lab-scale experiments, the sulfide concentration in a precipitator was controlled at a prespecified pS value by manipulating the flow from a buffer vessel. Batch tests showed that the optimal condition for zinc sulfide precipitation is at a sulfide concentration of 10 215 mole/l (pS 15). Experiments with the precipitator showed that the sulfide concentration highly deviates from a given setpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 19 publications
(18 reference statements)
0
27
0
1
Order By: Relevance
“…König et al [19] obtained concentrations below 0.1 ppm when titrating zinc with Na 2 S at pH 6. Therefore, zinc titrations indicate that zinc is not efficiently removed at low pH (3 and 4) ( Table 2).…”
Section: Titrationsmentioning
confidence: 98%
See 1 more Smart Citation
“…König et al [19] obtained concentrations below 0.1 ppm when titrating zinc with Na 2 S at pH 6. Therefore, zinc titrations indicate that zinc is not efficiently removed at low pH (3 and 4) ( Table 2).…”
Section: Titrationsmentioning
confidence: 98%
“…For the first two, commercially available devices were used, while for pS a proportional integral (PI) feedback control strategy was developed. In this feedback controller, the process variable pS is measured in the reactor and the manipulated variable Q sulf (sulfide flow) is adjusted using the deviation (ε(t)) between the measured pS and a predefined pS set-point [19]. In general, the feedback controller parameters should be related to the process parameters.…”
Section: Control Strategymentioning
confidence: 99%
“…Consequently, there should be some excess of sulphide ions, which requires an appropriate control strategy for the H 2 S or Na 2 S supply to the metal rich wastewater. König et al [8] found that a relatively simple PI control strategy using a pS electrode suffices. For other metals, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The sulphide process realizes an almost zero-emission of heavy metals at low costs. Furthermore, selective precipitation of individual heavy metals can be realized by controlling the pH and pS [3,4,8]. This results in pure precipitates of metal sulphides that can be reused as a raw starting material in the metal industry.…”
Section: Introductionmentioning
confidence: 99%
“…Supersaturation, achieved by adding more sulphide, could speed up the precipitation process (Veeken et al, 2003). Furthermore, the feeding of the Na 2 S might affect the precipitation process, as König et al (2006) tested, a precipitator with a titration mode may be more appropriate for lowering the value of MOR, although this is not suitable for large-scale application.…”
Section: Cu Recovery From the Amdmentioning
confidence: 99%